Interpersonal Rejection 2006
DOI: 10.1093/acprof:oso/9780195130157.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of Romantic Rejection

Abstract: This chapter revolves around the kind of rejection accompanied by special feelings toward the person who initiated the refusal of an aspiring lover's proposal. Discussed here are the perception differences of the rejected and the rejector, as well as their corresponding implications. Unreciprocated feelings result in self-degradation, despair, and lack of enthusiasm to engage in future relationships. Maintenance of a certain level of friendship or acquaintance can be hindered by the awkward aftermaths of misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…A decrease in selfesteem might function as an evolved psychological adaptation, which signals the loss of potential mates and reproductive resources and also signals a decrease in one's own perceived genetic value as a romantic partner (Shackelford, 2001). Similar to results found in this study, romantic rejection can reduce reported levels of self-esteem and mood (Baumeister & Dhavale, 1995). Indeed, the absence of flirting from members of the opposite gender may be enough to signal rejection (Trost & Alberts, 2006).…”
supporting
confidence: 67%
“…A decrease in selfesteem might function as an evolved psychological adaptation, which signals the loss of potential mates and reproductive resources and also signals a decrease in one's own perceived genetic value as a romantic partner (Shackelford, 2001). Similar to results found in this study, romantic rejection can reduce reported levels of self-esteem and mood (Baumeister & Dhavale, 1995). Indeed, the absence of flirting from members of the opposite gender may be enough to signal rejection (Trost & Alberts, 2006).…”
supporting
confidence: 67%
“…In fact, many of the would-be lovers' memories were bittersweet and warm (Bratslavsky et al 1998). For the would-be lover, the situation does not always have to end badly, because the would-be lover perceives outcomes ranging from very negative to very positive (Baumeister and Dhavale 2001). Conversely, most rejectors had very negative recollections and feelings about the entire episode (Bratslavsky et al 1998).…”
Section: Results Of Unrequited Love Experiencesmentioning
confidence: 99%
“…Similarly, the early stages of a potential romantic relationship also provide fertile soil for unrequited love involvements to develop. Unrequited love can thus be considered a "false start" on the way to mutual love (Baumeister and Dhavale 2001). Two people may develop a mutual interest in one another and after a few interactions, one person's feelings diminish, whereas the other's flourish (Bratslavsky et al 1998).…”
Section: Why Do Unrequited Love Experiences Occur?mentioning
confidence: 99%
See 1 more Smart Citation
“…It indeed frustrates the most essential and primitive social bond, that is romantic affiliation (see Stinson, Holmes, & He, 2011). Thus, this rejection can have relevant physical and psychological consequences, by posing a serious threat to peopleʼs self-image (Slotter, Gardner, & Finkel, 2010) and deeply affecting their well-being (e.g., Monroe, Rohde, Seeley, & Lewinsohn, 1999; see also Baumeister & Dhavale, 2001 for a review). Further, some works suggested possible differences in how men and women react to this form of rejection or relationship break-ups.…”
Section: The Consequences Of Romantic Rejectionmentioning
confidence: 99%